La conceptualizacón moderna del poder desde el cinismo clásico. Reflexiones sobre"El Dedo de Diógenes" de Pablo Oyarzún - Retamal, Christian (Revista de Filosofía, 2007)
The present paper approaches the crisis of modernity from the perspective of classic cynicism. We find in Pablo Oyarzún’s book, El dedo de Diógenes: La anécdota en filosofía, a fundamental interpretation that allows one to question the modern conceptualization with respect to power. In addition, the contributions of cynicism are analyzed from the perspective of critical theory.